EVALUASI PROGRAM PEMBANGUNAN INFRASTRUKTUR PERDESAAN (PPIP) TERHADAP PENINGKATAN EKONOMI MASYARAKAT DI KECAMATAN LEMBO KABUPATEN MOROWALI UTARA (Studi Kasus: Desa Korobonde, Korowou,Wawopada - Krenhazia, Yemim (Katalogis, 2016)
AbstractRural Infrastructure Development Program (PPIP) is a program of rural infrastructure development assistance directed to boost the rural economy. PPIP implemented participation where the public can choose the desired infrastructure. With a participatory approach, the infrastructure priorities depend on society's ability to vote. This study aimed to evaluate the results of the implementation of the PPIP using evaluation criteria Dunn effectiveness, efficiency, adequacy, equity, rensponsiveness, appropriateness and also to see the benefits of the program on improving the local economy by taking a case study in the village Korobonde, Korowou and Wowopada District of Lembo, This study uses descriptive qualitative data analysis techniques using Likert Scale. Results showed that the Rural Infrastructure Development program has been able to increase public access, yet the program has not been able to increase the welfare of the poor.